2014
DOI: 10.1055/s-0034-1389993
|View full text |Cite
|
Sign up to set email alerts
|

From β-Catenin to ARM-Repeat Proteins in Adrenocortical Disorders

Abstract: Armadillo-containing proteins (ACPs) are a large family of evolutionary conserved proteins, characterized by the tandem repeat copy of a 42 amino acids motif, which forms a 3 dimensional protein-protein interaction domain. This permits ACPs to interact with plenty of partners and consequently, most of these proteins have several independent cellular roles. Perhaps the most well-known protein of this family is β-catenin, which is crucial in the regulation of development and adult tissue homeostasis through its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
(81 reference statements)
1
14
0
1
Order By: Relevance
“…Our group and others previously described ARMC5 inactivating mutations as a frequent cause of macronodular adrenal hyperplasia and Cushing syndrome (25)(26)(27)(28)(29). In the present study, we also identified predicted damaging germline ARMC5 gene mutations in 10.7% of patients with PA (six of 56 patients).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our group and others previously described ARMC5 inactivating mutations as a frequent cause of macronodular adrenal hyperplasia and Cushing syndrome (25)(26)(27)(28)(29). In the present study, we also identified predicted damaging germline ARMC5 gene mutations in 10.7% of patients with PA (six of 56 patients).…”
Section: Discussionsupporting
confidence: 76%
“…We and others recently described germline and somatic mutations in an armadillo repeat containing 5 (ARMC5) gene that causes hypercortisolism in primary macronodular adrenal hyperplasia (PMAH) (25)(26)(27)(28)(29). ARMC5 maps to 16p11.2 and is likely to be a tumor-suppressor gene (27). Tumors caused by mutations in ARMC5 are likely to be polyclonal: both alleles of ARMC5 carry mutations at the somatic and germline levels.…”
mentioning
confidence: 99%
“…Activation of Wnt/β-catenin pathway is one of the major features in APA, being found in at least two-thirds of APA (Boulkroun et al 2011, Berthon et al 2012, Berthon & Stratakis 2014. The Wnt/β-catenin pathway plays an important role in embryonic development, stem cell maintenance and differentiation in many tissues, especially normal adrenal development and tumorigenesis (El Wakil & Lalli 2011).…”
Section: Mutations Affecting β-Catenin Activationmentioning
confidence: 99%
“…ARMC5 belongs to the large family of armadillo (ARM)-repeat-containing proteins, of which the best-known member is β-catenin and is likely to be a tumor-suppressor gene (Berthon & Stratakis 2014). ARMC5 inactivation appears to affect steroidogenesis.…”
Section: Armc5 Variantsmentioning
confidence: 99%
“…However the function of ARMC5 remains unknown as do the mechanisms of the inactivating mutations of ARMC5 involved in development of adrenal macronodular hyperplasia (Berthon & Stratakis 2014).…”
Section: Ectopic Expression Of Corticotropin In Pmahmentioning
confidence: 99%